Identificación de la toxoplasmosis mediante pruebas serológicas en felinos - Quinga Cedeño, Patricio Alexander (2022)
Toxoplasmosis is one of the zoonotic diseases that causes neonatal death which is mainly transmitted by cats and has caused 327 deaths and hospitalization for FBD with about 4428 deaths. Therefore early detection of the disease is very important, which causes multiple damages to public health, performing different types of serological tests, which are explained in this document, among which are the Sabin-Feldman (SF) test, indirect hemagglutination (HAI), indirect immunofluorescence (IIF) and ELISA. These techniques are presented in this document, considering that there are some developed for rapid methods and others that take a longer time, but to carry out the diagnostic techniques it is necessary that certain criteria be met, such as that in cats the lung picture, enzyme tests and leukocyte count that may indicate tissue damage. Serological evidence of recent or past infections (IgG and IgM) Demonstration of the presence of the parasite in tissues or fluids through biopsies or extraction of cerebrospinal fluid, respectively.